New record of Tettigarctidae (Insecta, Hemiptera, Cicadoidea) from the Lower Cretaceous of Brazil - Menon, Federica (Zootaxa, 2005)
Tettagalma striata, new genus and species of Tettigarctidae (Hemiptera: Cicadoidea), is described from the Lower Cretaceous laminated limestones of the Crato Formation, Brazil. The new discovery represents the first certain record of this family in Brazil and confirms its presence in the Southern Hemisphere during the early Cretaceous. Architettix Hamilton, 1990, from the same formation, and all the taxa originally placed in Cicadoprosbolidae, are also included in Tettigarctidae, as the former is considered a synonym.